Kajian Konsep Modalities of Constraint Terhadap Pencegahan Konten Hate Speech sebagai Cybercrime di Indonesia - Pratiwi, Berliant; Kautsar, Izzy Al (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2022)
The purpose of this study is to examine the prevention of hate speech crimes which are disseminated through various public facilities through the perspective of the Modalities of Constraint concept, this research also examines Indonesia's position in interpreting freedom of expression. This study uses a normative juridical research method with a concept approach and statutory approach. The results of this study are (1) Indonesia adheres to the view of Freedom speech as liberty with restrictions on the content of the speech that is conveyed must not conflict with the unity and integrity principles. (2) Based on the four aspects of the Modalities of Constraint concept, Indonesia in its position to prevent hate speech crimes has a strong legal substance; it has norms of unity and gotong royong in society; it has adapted to the development of social media platforms; it already has a precise and measurable prevention pattern.